Seaweed derived bioactive metabolites for sustainable agriculture: Phytostimulatory effects, stress mitigation and soil remediation potential - Niharika, P; Mahendran, P P; Prabhaharan, J; Gurusamy, A; Prasanthrajan, M; Chandrakumar, K; Mohamed, M R A F (Plant Science Today, 2025)
Marine algae, commonly known as seaweeds, represent a largely untapped bioresource with diverse applications in food, industry, medicine and traditional botanical practices. Over the past few decades, their role in agriculture has gained significant attention due to the presence of bioactive compounds that confer multiple benefits to plants. Seaweed-derived products exhibit strong phytostimulatory properties, promoting enhanced seed germination, root and shoot development, nutrient uptake and overall crop yield across a variety of horticultural and agricultural field crops. Beyond acting as growth enhancers, these compounds serve as phytoelicitors, activating plant defense mechanisms that improve tolerance to biotic stresses such as pests and diseases, as well as abiotic stresses including drought, salinity and low temperatures. Seaweeds have also been reported as effective bioadsorbents, capable of immobilizing or removing pollutants such as heavy metals and organic contaminants from soils, thereby contributing to soil restoration and environmental remediation. The highly organic nature of seaweed extracts makes them ideally suited for organic and environmentally sensitive farming systems. Furthermore, their compatibility with other fertilizers and crop management practices enables seamless integration into conventional and integrated crop management programs aimed at sustainable agriculture. This review synthesizes current knowledge on metabolite profiles in different seaweed species and evaluates their functional effects in crop production systems. The existing scientific knowledge in this area has been systematically examined to guide further investigations and potential applications.